(untitled) (Journal of Engineering, 2011)
Pilot-scale dead end microfiltration membranes were carried out to determine the feasibility of the process for treating the oily wastewater which discharge from some Iraqi factories such as power station of south of Baghdad and the general company of petrochemical industries. Polypropylene membranes (cylindrical shape) with different pore diameters (1 and 5 micron) were used to conduct the study on micromembrane process. The variables studied are oil concentration (100 – 1000 ppm), feed flow rate (20 – 40 l/h), operating temperature (31 – 50°C) and time (0 – 3 h). It was found that the flux increases with increasing feed flow rate, temperature and pore size of membrane, and decreases with increasing oil concentration and operating time. It was found also that the effect of feed oil concentration has the greatest effect on the fouling of membrane among other variables. The percent rejection of oil improved significantly with decreasing oil concentration but decreased with increasing feed temperature, pore size of membrane and operating time. Feed flow rate has slightly effect on oil rejection. The type of oil used in this work is 20W-50 gasoline and diesel engine oil. A general model of dead end filtration mode has been successfully evaluated to explain fundamental mechanisms involved in flux decline during dead end microfiltration of oily water emulsions. Analysis of the fall in flux with time for the polypropylene membrane (5 μm) indicates that intermediate and standard pore models give the best prediction for experimental behavior. Empirical correlations for the prediction of the flux and percent reject of oil were determined in this study. These equations have the correlation coefficient 98.87% and 91.49% respectively.